1999
DOI: 10.1590/s0100-879x1999000100006
|View full text |Cite
|
Sign up to set email alerts
|

A polymerase chain reaction-based assay to identify genotype F of hepatitis B virus

Abstract: We have developed a polymerase chain reaction (PCR) assay which distinguishes genotype F from the other genotypes of hepatitis B virus (HBV). The method was used to characterize HBV strains isolated in urban areas of the Brazilian Amazon. DNA was amplified in 54 of a total of 78 HBsAg-positive serum samples, using universal, nongenotype-specific primers. Only 4 (7.4%) were identified as genotype F by our genotype-specific PCR assay. This proportion is notably lower than that previously reported in Argentina, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…These results are in agreement with the studies accomplished by TEDESCHI et al (1989) 38 and CHIARAMONTE et al (1991) 11 although they differ from other studies in which it has been observed higher indexes of detection for HBV-DNA by PCR 2,16,27 and Dot-blot 26 .…”
Section: Discussionsupporting
confidence: 90%
“…These results are in agreement with the studies accomplished by TEDESCHI et al (1989) 38 and CHIARAMONTE et al (1991) 11 although they differ from other studies in which it has been observed higher indexes of detection for HBV-DNA by PCR 2,16,27 and Dot-blot 26 .…”
Section: Discussionsupporting
confidence: 90%
“…W hen analyzing samples previously characterized by a monoclonal antibody technique compared with primers for genotype F, we identified genotype A as the most frequent, followed by D and F, which suggested that there was an over-estimation of genotype F in other studies because they used monoclonal antibodies to identify the serotypes 18 .…”
Section: Ethical Considerationsmentioning
confidence: 80%
“…Studies on the distribution of HBV genotypes in Brazil and the Amazon also show that in the northern region, genotype A is the most common, followed by genotype D and genotype F 12,[17][18][19] . However, other studies performed in the Brazilian Amazon revealed that genotype F is more prevalent [20][21][22] .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…A mixture of one sense primer PS1 (5 0 -CCATATTCTTGGGAACAAGA-3 0 , nt positions 2826-2845) and two antisense primers (S2, 5 0 -GGGTTTAAA-TGTATACCCAAAGA-3 0 , 819-841, and S22, 5 0 -GTATT-TAAATGGATACCCACAGA-3 0 , 819-841) was used. This was because, according to a previous study [Moraes et al, 1999], the simultaneous use of antisense primers S2 and S22, located at the same position on genome, would facilitate the amplification of all HBV genotypes. After an initial DNA denaturation for 3 min at 948C, amplification was for 30 cycles at 958C for 30 sec, 528C for 40 sec, and 728C for 2 min, followed by a final elongation for 7 min at 728C.…”
Section: Hbv Dna Detection and Genotypingmentioning
confidence: 98%